Balanced-force shim system for correcting magnetic-field inhomogeneities in the heart due to implanted cardioverter defibrillators - Hrovat, Mirko; Kolandaivelu, Aravindan; Wang, Yifan; Gunderman, Anthony; Halperin, Henry R.; Chen, Yue; Schmidt, Ehud J. (Frontiers in Medicine, 2024)
Background: In the US, 1.4 million people have implanted ICDs for reducing the risk of sudden death due to ventricular arrhythmias. Cardiac MRI (cMR) is of particular interest in the ICD patient population as cMR is the optimal imaging modality for distinguishing cardiac conditions that predispose to sudden death, and it is the best method to plan and guide therapy. However, all ICDs contain a ferromagnetic transformer which imposes a large inhomogeneous magnetic field in sections of the heart, creating large image voids that can mask important pathology. A shim system was devised to resolve these ICD issues. A shim coil system (CSS) that corrects ICD artifacts over a user-selected Region-of-Interest (ROI), was constructed and validated. Methods: A shim coil was constructed that can project a large magnetic field for distances of ~15cm. The shim-coil can be positioned safely anywhere within the scanner bore. The CSS includes a cantilevered beam to hold the shim coil. Remotely controlled MR-conditional motors allow 2mm-accuracy three-dimensional shim-coil position. The shim coil is located above the subjects and the imaging surface-coils. Interaction of the shim coil with the scanner's gradients was eliminated with an amplifier that is in a constant current mode. Coupling with the scanners' radio-frequency (rf) coils, was reduced with shielding, low-pass filters, and cable shield traps. Software, which utilizes magnetic field (B0) mapping of the ICD inhomogeneity, computes the optimal location for the shim coil and its corrective current. ECG gated single-and multiple-cardiac-phase 2D GRE and SSFP sequences, as well as 3D ECG-gated respiratory-navigated IR-GRE (LGE) sequences were tested in phantoms and N=3 swine with overlaid ICDs.Results: With all cMR sequences, the system reduced artifacts from >100ppm to <25ppm inhomogeneity, which permitted imaging of the entire left ventricle in swine with ICD-related voids. Continuously acquired Gradient recalled echo or Steady State Free Precession images were used to interactively adjust the shim current and coil location. Conclusion: The shim system reduced large field inhomogeneities due to implanted ICDs and corrected most ICD-related image distortions. Externally-controlled motorized translation of the shim coil simplified its utilization, supporting an efficient cardiac MRI workflow.